2018
DOI: 10.1111/1462-2920.14104
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of closely related, uncultivated Coxiella tick endosymbiont population genomes reveals clues about the mechanisms of symbiosis

Abstract: Understanding the symbiotic interaction between Coxiella-like endosymbionts (CLE) and their tick hosts is challenging due to lack of isolates and difficulties in tick functional assays. Here we sequenced the metagenome of a CLE population from wild Rhipicephalus sanguineus ticks (CRs) and compared it to the previously published genome of its close relative, CLE of R. turanicus (CRt). The tick hosts are closely related sympatric species, and their two endosymbiont genomes are highly similar with only minor diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 79 publications
4
43
0
Order By: Relevance
“…We used the bactericidal ofloxacin to suppress CLE, while other studies used rifampicin or tetracycline (bactericidal and bacteriostatic, respectively) which we found to be less effective in suppressing CLE. Interestingly, genomic evidence suggests that CLE from R. sanguineus may carry native resistance genes to tetracycline [by involvement of translation elongation factor G (Taylor and Chau, 1996;Tsementzi et al, 2018)], which could explain its relatively mild effect on CLE observed in our study. One re-occurring concern is a possible direct effect of the antibiotic contributing to the observed negative outcomes on fitness (see Li et al, 2018).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…We used the bactericidal ofloxacin to suppress CLE, while other studies used rifampicin or tetracycline (bactericidal and bacteriostatic, respectively) which we found to be less effective in suppressing CLE. Interestingly, genomic evidence suggests that CLE from R. sanguineus may carry native resistance genes to tetracycline [by involvement of translation elongation factor G (Taylor and Chau, 1996;Tsementzi et al, 2018)], which could explain its relatively mild effect on CLE observed in our study. One re-occurring concern is a possible direct effect of the antibiotic contributing to the observed negative outcomes on fitness (see Li et al, 2018).…”
Section: Discussionmentioning
confidence: 64%
“…The CLE 16S and tick 18S rRNA gene copies were subsequently quantified by SYBR green-based qPCR on a SteponePlus machine (Applied Biosystems, CA, United States) using target-specific primers for detection of CLE in Rhipicephalus turanicus, as previously described (434f-1004r; Lalzar et al, 2012Lalzar et al, , 2014. R. turanicus is a member of the R. sanguineus species complex and both associate with closely related CLEs matching in their 16S rRNA gene sequence (99.9% nucleotide identity, Tsementzi et al, 2018). Quantitation of the tick's rRNA gene was accomplished using a costume designed primer pair (673f-909r) designed using primer3 1 and tested under blastn algorithm in NCBI.…”
Section: Identification and Quantification Of Clementioning
confidence: 99%
See 1 more Smart Citation
“…First, in using sequence-based methods to confirm the identities of ticks (and their hosts), we avoid the problems of using morphological criteria alone, which can be problematic in tick identification and classification [61]. Second, in addition to simply detecting or identifying tick-borne pathogens and endosymbionts, we, like others [34,36], have used shotgun metagenomic sequencing to obtain in-depth genome-resolved characterisation of key bacteria from this setting. Third, in recovering genome sequences from an unexpected pathogens (canine parvovirus) and a previously unsequenced pathogen ( R. barbariae ), we have demonstrated the open-ended nature of diagnostic metagenomics [35].…”
Section: Discussionmentioning
confidence: 99%
“…Coxiella-like endosymbionts of Rhipicephalus sanguineus and R. turanicus have been recently assigned to a new candidate species Candidatus C. mudrowiae, on the basis of genome sequences derived from pools of ticks isolated in Israel [33,34]. We present genome sequences of Candidatus C. mudrowiae derived from individual Rhipicephalus sanguineus and R. turanicus ticks, which were harvested in Palestine.…”
Section: Discussionmentioning
confidence: 99%